Psychological characteristics of Korean children and adolescents with type 1 diabetes mellitus - Eunhe Cho; Sang Hoon Shin; So-Hee Eun; Ji-Yeon Kim; Hyo-Kyung Nam; Kee-Hyoung Lee; Young-Jun Rhie (Korean Society of Pediatric Endocrinology, 2013)
PurposeThis study investigates the behavioral and emotional characteristics of Korean children and adolescents with type 1 diabetes mellitus (T1DM) as compared to healthy controls, and examines whether their psychological status is associated with glycemic control, insulin regimens, or disease duration.MethodsA total of 37 Korean children and adolescents with T1DM, aged 6-17 years, and 38 sex- and age-matched healthy controls were included in this study. Psychological distress was assessed using the Korean child behavior checklist (K-CBCL) and children's depression inventory (CDI) after the subjects and their parents were interviewed.ResultsThe CDI and K-CBCL scores were significantly higher in T1DM subjects compared to normal controls. The T1DM subjects with "poorly controlled" blood glucose (glycosylated hemoglobin ≥8%) and "old patients" (disease duration ≥1 year) had a tendency to show higher CDI and K-CBCL scores. There were no significant differences in CDI and K-CBCL scores between the intensive and conventional insulin therapy groups.ConclusionChildren and adolescents with T1DM seem to have inferior psychological adjustment to their normal counterparts, which might be associated with glycemic control and disease duration. Psychological evaluation and intervention should be considered in the management of T1DM in children and adolescents.